Multiwavelength Transmission Spectroscopy Revisited for the Characterization of the Protein and Polystyrene Nanoparticle Interactions. Issue 1 (January 2013) - Serebrennikova, Yulia M.; Roth, Alison; Huffman, Debra E.; Smith, Jennifer M.; Lindon, Jack N.; Garcia-Rubio, Luis H.
Multiwavelength transmission ultraviolet-visible-near-infrared (UV-Vis–NIR) spectroscopy is an effective technique that has not yet been fully exploited for the characterization of products of protein and particle interactions. Here, it is explored by using bovine serum albumin and National Institute of Standards and Technology-traceable particle size standard having a nominal diameter of 20 nm. Adsorption of bovine serum albumin to the particles is quantitatively ascertained through its effect on the wavelength-dependent transmission spectra of protein and particle mixtures. The experimental results demonstrate that the changes induced in the transmission spectra of protein and particle mixtures because of protein adsorption on particles are detectable and consistent with the expectations set by the light-scattering theory. The size, structure, composition, and relative concentrations of the particle populations present in the protein-particle mixtures can be quantified. Given the considerable dynamic range of multiwavelength transmission UV–Vis–NIR spectroscopy for particle analysis and its real-time measurement capabilities, this type of spectroscopy can be effectively used for the characterization of the products of protein-particle interaction and for the continuous real-time monitoring of interaction processes.